CEARÁ’S INTERNATIONAL TRADE (1997-2012) IN HECKSCHER-OHLIN PERSPECTIVE - Costa, Rayssa Alexandre; Castro, Inez Silvia Batista (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
This paper aims to analyze the changes in Ceará’s foreign trade during the period 1997-2012, in terms of use of the available productive resources, trying to answer if Heckscher-Ohlin model explains Ceará’s international trade trajectory. According to the Heckscher-Ohlin Model, variation in the factor endowments plays a key role in the pattern of international trade, so this paper applies an empirical test from the perspective of the Heckscher-Ohlin Model. To this end, it was applied the technique of input-output, with the three factors of production: labor, capital and natural resources This approach is compatible with the version of the model with three factors tested by Hidalgo and Feistel (2006). The direct and indirect requirements of production factors were calculated in each sector and the classification of products according to the intensities of factors was based on the method of Triangles Appropriations. The results show that exports in Ceará are based on labor intensive goods, while imports are concentrated in capital intensive goods in most years, corroborating the Heckscher-Ohlin Model ideas.